Low‐flow veno‐venous extracorporeal carbon dioxide removal in the management of severe status asthmatics: a case report. (15th January 2015) - Tiruvoipati, Ravindranath; Haji, Kavi; Gupta, Sachin; Braun, Gary; Carney, Ian; Botha, John
Abstract: Status asthmaticus is a life‐threatening condition that requires intensive care management. Most of these patients have severe hypercapnic acidosis that requires lung protective mechanical ventilation. A small proportion of these patients do not respond to conventional lung protective mechanical ventilation or pharmacotherapy. Such patients have an increased mortality and morbidity. Successful use of extracorporeal membrane oxygenation (ECMO) is reported in such patients. However, the use of ECMO is invasive with its associated morbidity and is limited to specialised centres. In this report, we report the use of a novel, minimally invasive, low‐flow extracorporeal carbon dioxide removal device in management of severe hypercapnic acidosis in a patient with life threatening status asthmaticus.